The Archaeology of Sulawesi Current Research on the Pleistocene to the Historic Period - O'Connor, Sue; Bulbeck, David; Meyer, Juliet (Terra Australis, 2018)
The central Indonesian island of Sulawesi has recently been hitting headlines with respect to its archaeology. It contains some of the oldest directly dated rock art in the world, and some of the oldest evidence for a hominin presence beyond the southeastern limits of the Ice Age Asian continent. In this volume, scholars from Indonesia and Australia come together to present their research findings and views on a broad range of topics. From early periods, these include observations on Ice Age climate, life in caves and open sites, rock art, and the animals that humans exploited and lived alongside. The archaeology presented from later periods covers the rise of the Bugis kingdom, Chinese trade ceramics, and a range of site-based and regional topics from the Neolithic through to the arrival of Islam. This carefully edited volume is the first to be devoted entirely to the archaeology of the island of Sulawesi, and it lays down a baseline for significant future research. Peter Bellwood, Emeritus Professor, The Australian National University